The `Unfinished Business' of Malaysia's decolonisation: The origins of the Guthrie `Dawn Raid' - Yacob, S.; White, N.J. (Cambridge University Press, 2010)
In a `dawn raid' on the London Stock Exchange on 7 September 1981, the premiere British rubber and oil palm conglomerate in Malaysia, the Guthrie Corporation Limited, was taken into local control in less than four hours. This was the most dramatic Malaysian acquisition of a foreign company during the restructuring of the country's post-colonial economy during the 1970s and 1980s, and the Guthrie Dawn Raid remains a celebrated but, at the same time, contested juncture in contemporary Malaysian memory. Drawing upon a variety of sources-including original interviews and correspondence with key participants in, and observers of, the Guthrie Dawn Raid, as well as newly released British documents related to the Anglo-Malaysian events of September 1981-this article presents a new interpretation of the origins of this most iconic of Malaysian corporate takeovers. In particular, it stresses the long-term aspirations of a key (but often overlooked) figure within the late and post-colonial Malay bureaucratic and economic elite, Ismail Mohamed Ali. At the same time, the article emphasizes the specific requirements of Malaysia's New Economic Policy against the backdrop of burgeoning intra-Malaysian ethnic business competition.